Treatment patterns and survival in patients with early‐onset pancreatic cancer. Issue 19 (6th July 2021) - Saadat, Lily V.; Chou, Joanne F.; Gonen, Mithat; Soares, Kevin C.; Kingham, T. Peter; Varghese, Anna M.; Jarnagin, William R.; D'Angelica, Michael I.; Drebin, Jeffrey A.; O'Reilly, Eileen M.; Wei, Alice C.
Abstract : Background: Pancreatic cancer is uncommon in patients younger than 50 years, although its incidence is increasing. This study characterizes treatment utilization for early‐onset pancreatic cancer (EOPC) versus average‐age‐onset pancreatic cancer (AOPC) and identifies factors associated with failure to receive treatment. Methods: The National Cancer Data Base (NCDB) was queried for patients with EOPC (age < 50 years) or AOPC (age ≥ 50 years) from 2004 to 2016. Multinomial regression was used to compare utilization (single modality vs multimodal treatment with or without surgery vs no treatment) between EOPC and AOPC. Kaplan‐Meier methods were used to estimate overall survival (OS). Results: Of 248, 634 patients, 15, 710 (6.3%) had EOPC. There were more male patients (56% vs 50%), non‐White patients, and privately insured patients (61% vs 30%) with EOPC versus AOPC, without notable differences in clinical stage distribution. Patients with EOPC received more chemotherapy (38% vs 29%), surgery (9% vs 6.9%), chemoradiation (12% vs 9.2%), and multimodal treatment (21% vs 15%). The odds of receiving multimodal curative therapy were significantly higher for patients with EOPC versus patients with AOPC after adjustments for confounders (odds ratio, 3.89; 95% confidence interval [CI], 3.66‐4.15; P < .001). Nineteen percent of patients with EOPC, in contrast to 39% of patients with AOPC, received no treatment. Patients with AOPC more frequently declined chemotherapy (15% vs 9.5%). One‐year OS was higher for EOPC versus AOPC across each stage (0/I/II, 72% [95% CI, 71%‐74%] vs 53% [95% CI, 53%‐54%]; III, 48% [95% CI, 45%‐50%] vs 38% [95% CI, 37%‐38%]; IV, 25% [95% CI, 24%‐26%] vs 15% [95% CI, 15%‐15%]) and treated patients (0/I/II, 75% [95% CI, 74%‐77%] vs 64% [95% CI, 63%‐64%]; III, 51% [95% CI, 49%‐54%] vs 47% [95% CI, 47%‐48%]; IV, 29% [95% CI, 28%‐31%] vs 23% [95% CI, 23%‐24%]). Conclusions: Patients with EOPC receive more oncologic therapy than patients with AOPC, although the intensity, type, and duration of chemotherapy are not available in the NCDB; however, 19% and 39%, respectively, receive no therapy. Underutilization may explain suboptimal oncologic outcomes. Efforts to improve access and treatment utilization in all age groups are warranted. Abstract : Patients with early‐onset pancreatic cancer receive more oncologic therapy than older patients; however, treatment underutilization remains substantial for all age groups. Efforts to improve access and treatment utilization may improve survival.